Analisis Stabilitas Dinding Penahan Tanah Pada Pembangunan Jalan Inspeksi Waduk Brigif - Yelvi; Muhammad Rifqi Aryadi (Politeknik Negeri Jakarta, 2022)
The construction of the inspection road located in the Brigif retention pond was directly crossed by the Krukut River. For safety and comfortable road traffic against sliding, it would need a redesign of the slope of road in order to produce a safety factor (SF) ≥ 1,25 for static condition and SF ≥ 1,10 for dynamic condition. Slope conditions are considered when High Water Level (HWL) and Low Water Level (LWL) conditions. This analysis was carried out by using of manually calculations and SLOPE/W. Both assessment using the Simplified Bishop Method. The results shows that when HWL in static conditions is 3,20 for manual calculations and 2,48 for SLOPE/W. Then, when HWL conditions with the dynamic condition is 1,88 for manual calculations and 1,72 for SLOPE/W. In LWL of static conditions is obtained of 3,13 for manual calculations and 2,58 for SLOPE/W. The results of the analysis of SF LWL with dynamic conditions is 2,20 for manual calculations and 1,79 for SLOPE/W. It can be concluded partially that the slope condition is stable. Furthermore, to prevent the scouring effect on retaining walls on the slopes is used gabion. Stability safety factor (SF) for overturning is 4,25 ≥ 2; for sliding is 1,59 ≥ 1,5; and for the bearing capacity is 825,31 kN/m ≥ 378 kN/m. Overall stability analysis is shown that the slope with the reinforced with gabion system is able to retain the overturning, sliding and bearing capacity.